Bauhaus effects in art, architecture, and design - James-Chakraborty, Kathleen, 1960-; Kriebel, Sabine (Routledge, 2022)
"Bringing together an international team of scholars, this book offers new perspectives on the impact that the Bauhaus and its teaching had on a wide range of artistic practices. Three of the fields in which the Bauhaus generated immediately transformative effects were housing, typography, and photography. Contributors go further to chart the surprising relation of the school to contemporary developments in hair-styling and shop window display in unprecedented detail. New scholarship has detailed the degree to which Bauhaus faculty and students set off around the world, but it has seldom paid attention to its impact in communist East Germany or in countries like Ireland where no Bauhäusler settled. This wide-ranging collection makes clear that, a century after its founding, many new stories remain to be told about the influence of the twentieth century's most innovative arts institution. The book will be of interest to scholars working in art history, design history, photography and architectural history"- Resumé vydavatel
Keywords: Bauhaus; dějiny umění -- od 1945; dějiny umění -- 1890-1945; moderní architektura -- dějiny -- 1890-1945; dějiny architektury -- od 1945; umění -- Evropa; design -- dějiny; dějiny fotografie; grafika; typografie; history of art -- from 1945; history of art -- 1890-1945; modern architecture -- history -- 1890-1945; history of architecture -- from 1945; art -- Europe; design -- history; history of photography; prints; typography; elektronické knihy; kolektivní monografie; electronic books; collective monographs